Sosialisasi Hukum Akibat Hukum Dan Upaya Pencegahan Judi Online Pada Remaja - Suriani Suriani; Aldi Pratama Situmorang; Juliana Mangunsong; Nurul Akmal; Patria Sahdan (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This study aims to investigate the role of legal socialization at Vocational High School (SMK) Taman Siswa Kisaran in preventing online gambling practices among adolescents, as well as to understand the legal implications that adolescents may face when involved in such activities. The research method employed is a qualitative approach, gathering data through interviews with teaching staff, students, and legal experts, along with observation of the legal socialization activities conducted at the school. The findings indicate that SMK Taman Siswa Kisaran has implemented various legal socialization activities, including workshops, seminars, and extracurricular activities, to enhance students' understanding of the legal consequences of online gambling. However, challenges in the implementation of legal socialization were identified, such as resource constraints and lack of support from relevant parties. Potential legal repercussions for adolescents include criminal penalties, fines, and long-term consequences related to criminal records. Therefore, this study highlights the importance of the school's role in disseminating information about the laws related to online gambling to adolescents, emphasizing the need for greater support from the school, government, and other relevant institutions to enhance prevention efforts. The implications of this research include the development of more effective legal socialization strategies and the necessity for collaborative efforts among various stakeholders to address the issue of online gambling among adolescents. Thus, this study underscores the urgency and relevance of prevention efforts against online gambling practices among adolescents through legal socialization approaches in the educational environment.